1998
DOI: 10.1088/0029-5515/38/11/305
|View full text |Cite
|
Sign up to set email alerts
|

A tritium catalytic fusion reactor concept

Abstract: The performance of deuterium targets with small tritium seeding is analysed. The objective is to take advantage of the features of fusion reactivity ratios for very high burning temperatures in order to minimize tritium needs and to reduce the ignition temperature as much as possible. It is found theroretically and computationally that there is a regime for deuterium-tritium DTx plasmas (with x ≈ 0.03) where the final content of tritium in the pellet debris is the same as the initial contents in the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In that case, the mechanical expansion loss is negligible if the fusion burn propagation is supersonic, but heat conduction losses to the surrounding cold fuel must be included. Earlier estimates [3,5] indicated that both models give very similar results on ignition requirements and burnup performance.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In that case, the mechanical expansion loss is negligible if the fusion burn propagation is supersonic, but heat conduction losses to the surrounding cold fuel must be included. Earlier estimates [3,5] indicated that both models give very similar results on ignition requirements and burnup performance.…”
Section: Introductionmentioning
confidence: 95%
“…Very high ignition temperatures are one of the main problems in advanced fuel fusion targets [1]. It has been demonstrated that adding a small amount of tritium can reduce the ignition temperature of deuterium and of advanced fuel inertial fusion targets [2][3][4][5]. Tritium will probably be the most significant radiological problem in future DT fusion reactors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation